1989
DOI: 10.1111/j.1365-3113.1989.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and nomenclature of five hitherto inadequately‐known genera of mealybugs (Homoptera: Coccoidea: Pseudococcidae)

Abstract: The type‐species of four genera of Pseudococcidae are studied. Fonscolombia Lichtenstein is redefined, the type‐species, Fonscolombia graminis Lichtenstein is assigned to the Pseudococcidae, redescribed and a lectotype designated. Laboulbenia Lichtenstein is accepted as an objective synonym of Antonina Signoret. Tetrura Lichtenstein (non: Lesson) is accepted as an objective synonym of Coccura Sulc. The adult female of the material of this species which Lichtenstein misidentified as Tetrura rubi (Schrank) is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 4 publications
0
48
0
2
Order By: Relevance
“…Asadeh and Mosaddegh (1991), Ben-Dov (1994), Ben-Dov et al (2013), Cox (1989), Kaussari (1946), Kozár et al (1996), Moghaddam (2006, 2009, 2013) and Williams and Moghaddam (2000).…”
Section: Family Pseudococcidaementioning
confidence: 99%
See 2 more Smart Citations
“…Asadeh and Mosaddegh (1991), Ben-Dov (1994), Ben-Dov et al (2013), Cox (1989), Kaussari (1946), Kozár et al (1996), Moghaddam (2006, 2009, 2013) and Williams and Moghaddam (2000).…”
Section: Family Pseudococcidaementioning
confidence: 99%
“…Ben-Dov (1994), Ben-Dov et al (2013), Cox (1989), Cox and Ben-Dov (1986), Kozár et al (1996), Lotfalizadeh and Ahmadi (2000), Moghaddam (2006, 2009, 2010, 2013) and Williams and Moghaddam (1999).…”
Section: Family Pseudococcidaementioning
confidence: 99%
See 1 more Smart Citation
“…Mealybugs are characterized by the white mealy or powdery wax that covers the soft body of these insects Within the Phenacoccinae subfamily, the genus Fonscolombia Lichtenstein is characterized in having; (i) 6-8 segmented antennae; (ii) well-developed legs; (iii) claw with or without denticle; (iv) quinquelocular pores present or absent on venter and (v) reduced cerarii number (1-6) in posterior abdominal segments (Ben-Dov & Matile-Ferrero, 1989;Danzig, 2007). Ben-Dov & Matile-Ferrero (1989) found that the nominal type species, Coccus radicumgraminis Fonscolombe, was a misidentification by Lichtenstein of Fonscolombia graminis Lichtenstein (1877). It is now established that Fonscolombia graminis Lichtenstein is the type species and the genus Fonscolombia Lichtenstein is the accepted name (ICZN, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…El citado autor describe a las hembras adultas de color púrpura, y cubiertas con filamentos blancos de consistencia cerosa; además hace referencia a un predador y un parasitoide que la controlan. Sin embargo Phenacoccus aceris (Signoret) que es muy común en las Regiones Neártica y Paleártica, no ha sido encontrado hasta el momento en la región Neotropical, (Williams & Granara de Willink, 1992;Ben-Dov, 1994 …”
Section: Introductionunclassified